Development and testing of a questionnaire to measure patient satisfaction with intermediate care. Issue 5 (30th October 2006) - Wilson, A; Hewitt, G; Matthews, R; Richards, S H; Shepperd, S
Abstract : Background: Individual trials have suggested high levels of general patient satisfaction with intermediate care, but this topic has not been examined in detail. Aims: To identify the key elements of patient satisfaction with intermediate care, and to see whether these can be validly measured using a questionnaire. Method: A questionnaire was developed on the basis of a literature review and piloting with patients and staff on participating schemes (phase I). In phase II, the questionnaire was tested for validity and reliability in a group of patients recently discharged from two "hospital-at-home" intermediate-care schemes. In phase III, a shortened version of the questionnaire was psychometrically tested in five sites taking part in a national evaluation of intermediate care. Results: 96 patients with an average age of 76.5 years took part in phase II. Test–retest reliability was evaluated by repeating the questionnaire 2 weeks later in a subsample of 42 patients. This was "moderate" (κ 0.4–0.6) for 12 questions, "fair" (κ 0.2–0.4) for 6 questions and "poor" (κ 0.1–0.2) for 5 questions. Scores correlated well with the Client Satisfaction Questionnaire (Spearman's r = 0.75, p<0.001). 843 patients (57% of those eligible) from five intermediate-care schemes took part in phase III. Principal components analysis suggested six factors or subscales: general satisfaction, affective response, cognitive response, timing of discharge, coordination after discharge, and access to pain relief, although the last three factors comprised only one question each. The intraclass correlation coefficients in the first three subscales varied from 0.82 to 0.89. Scores for all subscales differed by scheme, suggesting construct validity. Only one question (on general satisfaction) was found to be redundant. Conclusion: The questionnaire, with some minor amendments to improve performance, could be used as a validated tool for audit and research in intermediate care. An amended version and scoring programme is available from us on request.